SINTESIS DAN KARAKTERISASI FT-IR MATERIAL GIANT DIELECTRIC CCTO DENGAN METODE REAKSI PADATAN - Siska Febriana; Kamsul Abraha (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Synthesis of giant dielectric material CaCu3Ti4O12, commonly called CCTO, using a solid-state reaction method has  been  done. The technique includes of mixing, compacting and heating such as calcination  and  sintering.  The  three  types  of  starting  powders : CaCO3, CuO and TiO2 were mixed then calcinated at 1100  and sintered for different temperatures at 500 , 700  and 900 . The sintered powders were characterized by X-ray diffraction (XRD) for investigate the cristalinity phase,  FT-IR spectroscopy  and  grain  size  measurement. X-ray  diffraction results   show that CCTO synthesized with sintering treatment give material a better crystallinity than without using sintering treatment. FT-IR characteristic spectra show the main absorption at wavenumber 447,49 for 500 , 700  and 900  sintered powder that indicate the vibrations of vTi-O-Ti type. Furthermore, the vTi-O  type vibrations   appear at   wavenumber 509,21 and 555,5 ; 516,92 and 570,93 ; 524,64 and 578,64 for  500 , 700  and 900  sintered powder respectively. However, the results of grain size calculation point out that the grain size increases with increasing sintering temperature.Keywords : Solid-state reaction, X-ray diffraction, FT-IR spectroscopy.